Creating social trust in post-socialist transition - Kornai, János (Palgrave Macmillan, 2004)
Cone of the central characteristics of socialist states and societies has been the absence of trust--between the state and the citizens, and then among citizens themselves. The process of developing trust is thus a major issue facing post-Socialist countries, and this book brings together a group of leading scholars to examine barriers to and bulwarks of trust in theoretical, cross-national, and topical perspectives. From the distinctive paradox of illegal organizations--such as the Mafiya--relying on trust within but undermining it without, to the effects of transparency, the authors examine the bases of trust and the effects of its presence or absence. Throughout the analysis is grounded in the interaction of individuals and their social, political, and economic environments.